A Documentation Framework for Sound in Time-based Media Installation Art. Issue 2 (3rd July 2021) - Brost, Amy
ABSTRACT: Perhaps because the visual arts predominate in museum collections, conservation documentation methods for audio in time-based media installation art are less developed than those for video. However, the aural elements are equally complex, both technically and creatively. This paper proposes a framework for documenting sound in time-based media installations, from the artist's vision for the listener experience of the artwork to its realization in the exhibition space. This documentation framework was applied to one artwork, The Visitors (2012) by Ragnar Kjartansson, as a case study. The framework and excerpts from the case study show how documentation focused on sound elements can yield unique insights about an artwork. For time-based media works that foreground sound, conservators must be conversant with sound physics, acoustics, audio engineering, and sound design so that they can have productive conversations with artists, sound professionals, and other stakeholders in order to create meaningful documentation of the significant aural properties of an artwork for the future. In this way, conservators can approach time-based media installations not only attending to how they look, but also to how they sound.